Sampling Jitter in Audio A/D Converters - KULKA, Zbigniew (Archives of Acoustics, 2011)
This paper provides an overview of the effects of timing jitter in audio samplinganalog-to-digital converters (ADCs), i.e. PCM (conventional or Nyquist sampling)ADCs and sigma-delta () ADCs. Jitter in a digital audio is often defined as short-term fluctuations of the sampling instants of a digital signal from their ideal positionsin time. The influence of the jitter increases particularly with the improvements inboth resolution and sampling rate of today’s audio ADCs. At higher frequenciesof the input signals the sampling jitter becomes a dominant factor in limiting theADCs performance in terms of signal-to-noise ratio (SNR) and dynamic range (DR).